Selection criteria for early breast cancer patients in the DBCG proton trial – The randomised phase III trial strategy - Line Bjerregaard Stick; Ebbe Laugaard Lorenzen; Esben Svitzer Yates; Carmel Anandadas; Karen Andersen; Cynthia Aristei; Orla Byrne; Sandra Hol; Ingelise Jensen; Anna M. Kirby; Youlia M. Kirova; Livia Marrazzo; et al. (Clinical and Translational Radiation Oncology, 2021)
Background and purpose: Adjuvant radiotherapy of internal mammary nodes (IMN) improves survival in high-risk early breast cancer patients but inevitably leads to more dose to heart and lung. Target coverage is often compromised to meet heart/lung dose constraints. We estimate heart and lung dose when target coverage is not compromised in consecutive patients. These estimates are used to guide the choice of selection criteria for the randomised Danish Breast Cancer Group (DBCG) Proton Trial. Materials and methods: 179 breast cancer patients already treated with loco-regional IMN radiotherapy from 18 European departments were included. If the clinically delivered treatment plan did not comply with defined target coverage requirements, the plan was modified retrospectively until sufficient coverage was reached. The choice of selection criteria was based on the estimated number of eligible patients for different heart and lung dose thresholds in combination with proton therapy capacity limitations and dose–response relationships for heart and lung. Results: Median mean heart dose was 3.0 Gy (range, 1.1–8.2 Gy) for left-sided and 1.4 Gy (0.4–11.5 Gy) for right-sided treatment plans. Median V17Gy/V20Gy (hypofractionated/normofractionated plans) for ipsilateral lung was 31% (9–57%). The DBCG Radiotherapy Committee chose mean heart dose ≥ 4 Gy and/or lung V17Gy/V20Gy ≥ 37% as thresholds for inclusion in the randomised trial. Using these thresholds, we estimate that 22% of patients requiring loco-regional IMN radiotherapy will be eligible for the trial. Conclusion: The patient selection criteria for the DBCG Proton Trial are mean heart dose ≥ 4 Gy and/or lung V17Gy/V20Gy ≥ 37%.